2022
DOI: 10.1111/jam.15683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antimicrobial susceptibility of Corynebacterium pseudotuberculosis isolated from skin abscesses of native Korean goats (Capra hircus coreanae)

Abstract: Aims: This study aimed to investigate the molecular characterization and antimicrobial susceptibility of Corynebacterium pseudotuberculosis from skin abscesses of Korean native black goats (KNBG, Capra hircus coreanae) in South Korea. Methods and results: A total of 83 isolates were recovered from skin abscesses of KNBG. Of these isolates, 74 isolates were identified as C. pseudotuberculosis by phospholipase D (PLD) gene-based PCR assay. Each of the isolates possessed all 18 viru-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In addition, our analysis revealed low bootstrap values and intergroup divergence within biotype Ovis, consistent with previous studies that reported genetic diversity within biotype Ovis is independent of host and geographic origins [8,71]. This could be due to the fact that this study was conducted on sheep and goats in a smallholder production system where close coexistence or even common grazing and housing among different flocks is possible [60].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, our analysis revealed low bootstrap values and intergroup divergence within biotype Ovis, consistent with previous studies that reported genetic diversity within biotype Ovis is independent of host and geographic origins [8,71]. This could be due to the fact that this study was conducted on sheep and goats in a smallholder production system where close coexistence or even common grazing and housing among different flocks is possible [60].…”
Section: Discussionsupporting
confidence: 90%
“…However, the majority of these isolates demonstrated resistance to numerous of the 24 tested antimicrobials. Most previous studies on the antimicrobial susceptibility of C. pseudotuberculosis showed diverse prevalence and patterns [8,21,32,60], which has been attributed by some authors to regional variations in antimicrobial use, the availability of over-the-counter antibiotics without prescriptions, and levels of veterinary service provided [60]. In Egypt, antimicrobials are available over-thecounter and extensively used by smallholder breeders as prophylactics and/or growth promoters [22], which might explain the high resistance rate reported in this study.…”
Section: Discussionmentioning
confidence: 63%
“…In recent years, the prevalence of caseous lymphadenitis (CLA) has increased, particularly among goat breeders in Korea, as it has become endemic (Jung et al, 2015;Kong et al, 2019). Furthermore, the presence of C. pseudotuberculosis in animals within the herd causes the rapid spread of CLA (Pathirana et al, 2022). Previous studies only focused on the seroprevalence in which 57.30% (Jung et al, 2015) and 43.00% (Kong et al, 2019) animals were seropositive and isolating the causative agents, leaving a gap in understanding the risk factors contributing to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is a chronic infectious disease that can cause zoonosis. This bacterium can cause disease in sheep, goats, cattle and other animals [ 20 ]. Nodules of varying sizes can be observed in the spleen, containing yellowish case-like substances.…”
Section: Discussionmentioning
confidence: 99%